Mechanism of Rock Bursts Induced by the Synthetic Action of “Roof Bending and Rock Pillar Prying” in Subvertical Extra-Thick Coal Seams - Wu, Zhenhua; Pan, Peng-Zhi; Chen, Jianqiang; Liu, Xudong; Miao, Shuting; Yu, Peiyang (Frontiers in Earth Science, 2021)
When studying the rock burst mechanism in subvertical extra-thick coal seams in the Wudong coal mine in Xinjiang, China, most studies focus on rock pillars, while the effect of the roof on rock bursts is usually ignored. In this paper, a rock burst mechanism in subvertical extra-thick coal seams under the control of a "roof-rock pillar" is proposed. A theoretical analysis is first performed to explain the effect of roof-rock pillar combinations on rock bursts in coal seams. Numerical modeling and microseismic analysis are implemented to further study the mechanism of rock burst. The main conclusions are as follows: 1) During the mining of the B3+6 coal seam, an obvious microseismic concentration phenomenon is found in both the roof and rock pillar of B3+6. The rock bursts exhibited obvious directionality, and its main failure characteristics are floor heave and sidewall heave, but there will also be some failures such as shoulder socket subsidence in some parts. 2) The stress transfer caused by rock pillar prying is the main reason for the large difference in rock burst occurrence near the vertical and extra thick adjacent coal seams under the same mining depth. 3) Under the same cantilever length, the elastic deformation energy of the roof is much greater than that of the rock pillar, which makes it easier to produce high-energy microseismic events. With an increasing mining depth, the roof will become the dominant factor controlling the occurrence of rock bursts. 4) The high-energy event produced by the rock mass fracture near the coal rock interface easily induces rock bursts, while the high-energy event produced by the fracture at the far end of the rock mass is less likely to induce rock burst. 5) Roof deformation extrusion and rock pillar prying provide high static stress conditions for the occurrence of rock bursts in the B3+6 coal seam. The superposition of the dynamic disturbance caused by roof and rock pillar failure and the high static stress of the coal seam is the main cause of rock burst in the B3+6 coal seam.